Object Classification And Recognition Using Bag-Of-Words (BOW) Model - Mohd Ali, Nursabillilah; Soon, Wei Jun; Karis, Mohd Safirin; Md Ghazaly, Mariam; Mohd Aras, Mohd Shahrieel (Institute of Electrical and Electronics Engineers (IEEE), 2016)
-